Épopée biblique entre traduction poétique et commentaire exégétique - Anne Fraïsse (Cahiers d'Études du Religieux- Recherches Interdisciplinaires, 2009)
The adaptation in dactylic hexameters of the Christ’s life from the Gospel of Matthew is rich in teaching on the connections betwen this literary genre - the biblical epic - and the biblical text and the pagan literature. We see the birth of a Christian poetry which addresses a well-read readership, but in a historic context - under the emperor Constantin - in which is a wrong feeling of triumphant enjoyment from the Christians. It will be a question here of studying through two passages - the foreword and the episode of the storm - the shape and the sense which takes the work of rewriting of the Christian poet.